Maternal HIV-1 Disease Progression 18–24 Months Postdelivery According to Antiretroviral Prophylaxis Regimen (Triple-Antiretroviral Prophylaxis During Pregnancy and Breastfeeding vs Zidovudine/Single-Dose Nevirapine Prophylaxis): The Kesho Bora Randomized Controlled Trial - (:unkn) unknown (My University, 2012)
Background : Antiretroviral (ARV) prophylaxis effectively reduces mother-to-child transmission of human immunodeficiency virus type 1 (HIV). However, it is unclear whether stopping ARVs after breastfeeding cessation affects maternal HIV disease progression. We assessed 18–24-month postpartum disease progression risk among women in a randomized trial assessing efficacy and safety of prophylactic maternal ARVs.Methods : From 2005 to 2008, HIV–infected pregnant women with CD4 + counts of 200–500/mm 3 were ran- domized to receive either triple ARV (zidovudine, lamivudine, and lopinavir/ritonavir during pregnancy and breastfeeding) or AZT/sdNVP (zidovudine until delivery with single-dose nevirapine without postpartum prophylaxis). Maternal disease progression was defined as the combined endpoint of death, World Health Organization clinical stage 4 disease, or CD4 + counts of <200/mm3 .Results : Among 824 randomized women, 789 had at least 1 study visit after cessation of ARV prophylaxis. Following delivery, progression risk up to 24 months postpartum in the triple ARV arm was significantly lower than in the AZT/sdNVP arm (15.7% vs 28.3%; P = .001), but the risks of progression after cessation of ARV prophylaxis (rather than after delivery) were not different (15.0% vs 13.8% 18 months after ARV cessation). Among women with CD4 + counts of 200–349/mm3 at enrollment, 24.0% (95% confidence interval [CI], 15.7–35.5) progressed with triple ARV, and 23.0% (95% CI, 17.8–29.5) progressed with AZT/sdNVP, whereas few women in either arm (<5%) with initial CD4 + counts of ≥350/mm 3 progressed.Conclusions : Interrupting prolonged triple ARV prophylaxis had no effect on HIV progression following cessation (compared with AZT/sdNVP). However, women on triple ARV prophylaxis had lower progression risk during the time on triple ARV. Given the high rate of progression among women with CD4 + cells of <350/mm 3 , ARVs should not be
Keywords: African Research